Development of Student Worksheets Based on Argument-Driven Inquiry to Improve The Scientific Argumentation Ability - Dewannia Fariska Herman; Ulin Nuha; Zainur Rasyid Ridlo (Universitas Sebelas Maret, 2025)
Scientific argumentation plays a crucial role in science learning, yet many students face difficulties in constructing and justifying arguments based on evidence. Conventional teaching approaches often do not provide adequate opportunities for structured argumentation. Student Worksheets Based on Argument-Driven Inquiry (ADI) integrate argumentation into experimental activities, yet their use in topics such as vibrations, waves, and light remains underexplored. This study focuses on developing student worksheets based on ADI to enhance the scientific argumentation ability of eighth-grade students at MTsN 1 Jember. The research follows the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The worksheets underwent validation by three experts and were tested using observation sheets, student questionnaires, and pretest-posttest assessment. Findings indicate that the worksheets are highly valid, practical, and effective, with an N-gain score of 0.7, classified as high. These results suggest that integrating ADI-based worksheets into science instruction can foster students’ scientific argumentation ability